The skeleton: an overlooked regulator of systemic glucose metabolism in cancer? - Ronghe, Rucha; Tavares, Adriana A. S. (Frontiers in Oncology, 2024)
Recent discoveries demonstrated the skeleton’s role as an endocrine organ regulating whole-body glucose homeostasis. Glucose metabolism is critical for rapid cell proliferation and tumour growth through increasing glucose uptake and fermentation of glucose to lactate despite being in an aerobic environment. This hypothesis paper discusses emerging evidence on how bones can regulate whole-body glucose homeostasis with potential to impact on tumour growth and proliferation. Moreover, it proposes a clinical link between bone glucose metabolism and prognosis of cancer based on recent clinical trial data. Targeting metabolic pathways related with classic glucose metabolism and also bone metabolism, novel methods of cancer therapy and treatment could be developed. This paper objective is to highlight the need for future research on this altered metabolism with potential to change future management of cancer patients.